Factors associated with the acceptability of HPV Self-sampling for cervical cancer screening among Thai ethnic women in Pai, Mae Hong Son - Phuttipol Chaiprom; Patumrat Sripan; Linda Aurpibul; Woottichai Khamduang; Sayamon Hongjaisee; Amaraporn Rerkasem; Arunrat Tangmunkongvorakul; Kriengkrai Srithanaviboonchai (BMC Women's Health, 2026)
Abstract Background Cervical cancer remains a major public health problem worldwide particularly in low- and middle-income countries. Human Papillomavirus (HPV) self-sampling is a promising strategy to increase screening participation. However, evidence regarding its acceptability among Thai ethnic communities is limited. This study aimed to estimate the proportion of acceptability of HPV self-sampling for cervical cancer screening among the ethnic women living in border areas of Thailand and determine its associated factors. Methods A cross-sectional study was conducted from January to May 2024 among 341 ethnic women aged 30–60 years, who held Thai citizenship and residing in Pai, Mae Hong Son, Thailand. A questionnaire assessed demographics, healthcare accessibility, knowledge about HPV and cervical cancer, and attitudes toward cervical cancer screening. Acceptability of self-sampling was defined as willingness to accept self-sampling alone or both self-sampling and clinician-based sampling. Factors associated with acceptability were analysed using univariable and multivariable binary logistic regression analyses. Results The median age of participants was 43 years (interquartile range: 36–49). Most of them were 185 (54%) Karen, followed by 83 (24%) Lisu, 50 (15%) Hmong, and 23 (7%) Lahu. Overall, 200 (58%) of participants accepted HPV self-sampling. In multivariable analysis, being of Lisu (adjusted odds ratio(aOR) = 3.12, 95% confidence interval (CI): 1.09–8.91), Hmong (aOR = 9.03, 95%CI: 1.09–8.91), or Karen (aOR = 3.86, 95%CI: 1.42–10.45) compared with Lahu, never undergone cervical cancer screening (aOR = 2.65, 95%CI: 1.43–4.91), and living within 3 km of a healthcare unit (aOR = 2.54, 95%CI: 1.55–4.16) were associated with higher acceptability of HPV self-sampling. In contrast, a higher positive attitude toward cervical cancer screening was associated with lower acceptability of self-sampling (aOR = 0.95, 95%CI: 0.91–0.98). Conclusions HPV self-sampling acceptability varies significantly across Thai ethnic women and was associated with prior screening experience, distance to healthcare facilities, and attitudes toward screening. Women with stronger positive attitudes toward cervical cancer screening showed lower acceptability. Further studies are needed to evaluate the implementation strategies for HPV self-sampling within cervical cancer screening programs, including approaches that provide clear, culturally appropriate communication and support women’s confidence in performing the test.